TINJAUAN YURIDIS KEPEMILIKAN PROPERTI DI INDONESIA - Muryani, Muryani (JURNAL LEGISIA, 2021)
Abstract Law Number 5 of 1960 concerning the Basic Regulation of Agrarian Principles (UUPA) confirms that only Indonesian citizens can have a full relationship with land. This provision is a manifestation of the principle of nationality in the ownership of property in the form of land. This research uses normative juridical research methods, the approach used is a legal approach from various laws and regulations related to the status of property rights for foreign nationals in Indonesia. This decision has certainly occurred a conflict of norms in the arrangement of granting rights to foreign nationals, to property in Indonesia, so what is the status of property ownership rights for Indonesian citizens and foreign citizens, only Indonesian citizens can have property rights to land because these provisions are a manifestation of the principle of nationality in property ownership in the form of land, Foreigners are not allowed to own title land even though because of inheritance as well as people who mix property, dual citizenship, namely foreign nationality in addition to being Indonesian citizens. Keywords: Overview, Property, Indonesian and Foreign Citizens